Diagnosing Non–Producers Non–Secretory Myeloma - Nina Nurarifah; Shinta Wardhani (Universitas Brawijaya, 2023)
Multiple myelomas (MM) is the proliferation of malignant plasma cells in the bone marrow, characterized by the production of monoclonal immunoglobulins that are secreted in the blood and urine. However, in 1 - 5% of cases, the protein is undetectable and defined as non-secretory type of myeloma. A 36-year-old woman presented with complaints of weakness in both legs so she could not walk. She also felt pain in the head, back, and thighs since one year before. Physical examination showed anemic conjunctiva, gibus as high as T4, hypoesthesia as high as T6 segment. She had anemia (Hb 10.2 g/dL), decreased kidney function (eGFR: 30 mL/min/1.73m2), and multiple lytic lesions in the calvaria, ribs, superior-inferior pubic ramus, and left humeral os in the 1/3 proximal to 1/3 distal. Protein electrophoresis and Bence Jonce protein were negative. There was no hypercalcemia, and bone marrow aspiration showed myelodysplasia syndrome. A thoracolumbar MRI showed an extradural solid mass and the histopathology examination result was plasmacytoma. Non-secretory MM was defined into two groups, non-producers and multiple non-secretory myeloma patients who produce tumor proteins but cannot be excreted. This patients was categorized as non-producers non-secretory MM because she did not show a protein that can be measured in blood nor urine, but has significant plasma cells in tissue biopsy. The absence of paraprotein in the blood does not rule out multiple myeloma. Suspicion of multiple myeloma needs to be increased in patients who have symptoms of CRAB (calcium, renal impairment, anemia, bone lytic).